(3OjhGf CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3GdCdajGJ bGd CHh JeGe jeOM NGdO Hf jRjO GdTjHGfi jG ehOY GdTO ajg GdhLfGheUGQY ajgG s
(3BNQgG (B:s
(3COei GdThb egLJg acja Ef JOei eG ajg Je OjhGf CHj JeGe s
(3QhGjI GdUhdi fbdJ Yf fSNI cJH SfI (B381s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs